PENGARUH PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 6 TAMBAK UKIR KECAMATAN KENDIT KABUPATEN SITUBONDO TAHUN PELAJARAN 2017/2018 - Rifqi Maulidi; Nur Holifatuz Zahro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2018)
The quality of language skills someone dependent on the quantity and quality of their vocabulary .The larger the vocabulary students the more good too skill read it. Mastery vocabulary students who still low it affects the ability to read understanding students. The formulation of a problem of the research is whether there is the influence of mastery of a vocabulary read understanding in the ability of the 4th grade student SDN 6 Tambak Ukir Kecamatan Kendit Situbondo district. The purpose of this study is to find the influence of mastery of a vocabulary read understanding in the ability of the 4th grade student SDN 6 Tambak Ukir Kecamatan Kendit Situbondo district. Approach research used in this research was the quantitative approach using the kind of research correlation a causal relation. The population of the research is SDN 6 Tambak Ukir. Sample used in this research was 4th graders SDN 6 Tambak Ukir some 20 students. Using techniques data collection tests and documentation. The analysis of data using analisis descriptive statistics by test a prerequisite analysis and the testing of hypotheses using analysis linear regression simple with SPSS program version 16. From the data analysis note that the value of the regression equation obtained by the y = 19,194 + 0,828x .It can be argued that hypothesis that was formulated accepted that is the mastery vocabulary on ability to read understanding SDN 6 Tambak Ukir Kecamatan Kendit Kabupaten Situbondo